2013
DOI: 10.1002/pds.3462
|View full text |Cite
|
Sign up to set email alerts
|

Use of selective serotonin reuptake inhibitors in pregnancy and cardiac malformations: a propensity‐score matched cohort in CPRD

Abstract: The results of this study are most compatible with no association between maternal use of SSRIs in early pregnancy and cardiac malformations or septal defects in the offspring. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
(47 reference statements)
1
46
0
Order By: Relevance
“…Among 27 articles that were selected for review, no consistent pattern has been observed in the reported risk of CHA. A slight increase in risk was found, particularly for paroxetine, in a number of studies in various countries (see Table S1) [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], but a number of other studies reported no increased risk (see Table S2) [23,24,25,26,27,28,29,30,31,32]. The dose of SRIs may also be an important determinant of the risk.…”
Section: The Risk Of Congenital Heart Anomalies (Cha) Associated Wmentioning
confidence: 99%
“…Among 27 articles that were selected for review, no consistent pattern has been observed in the reported risk of CHA. A slight increase in risk was found, particularly for paroxetine, in a number of studies in various countries (see Table S1) [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], but a number of other studies reported no increased risk (see Table S2) [23,24,25,26,27,28,29,30,31,32]. The dose of SRIs may also be an important determinant of the risk.…”
Section: The Risk Of Congenital Heart Anomalies (Cha) Associated Wmentioning
confidence: 99%
“…These proportions decreased to 40.63% (15 of the 37 per 1000 pregnancies) in the first trimester of pregnancy, 35.87% (six of the 16 per 1000 pregnancies) and 36.43% (six of the 17 per 1000 pregnancies) in respectively the second and third trimesters. Comparable proportions were observed for newly initiated category X drugs.…”
Section: Newly Initiated Drugsmentioning
confidence: 99%
“…[1][2][3] Studies concerning the adverse effects of SSRI exposure during gestation on the developing fetus have indicated an increased risk of various congenital malformations, [4][5][6][7][8][9] but inconsistencies between study results remain. [10][11][12][13][14] These could potentially be explained by indication bias where the effect of the drug and the indication are correlated and not fully accounted.…”
mentioning
confidence: 99%